Dispersal limitation induces long-term biomass collapse in overhunted Amazonian forests - Peres, Carlos A.; Emilio, Thaise; Schietti, Juliana; Desmouliére, Sylvain J.M.; Levi, Taal (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Tropical forests are the global cornerstone of biological diversity, and store 55% of the forest carbon stock globally, yet sustained provisioning of these forest ecosystem services may be threatened by hunting-induced extinctions of plant-animal mutualisms that maintain long-term forest dynamics. Large-bodied Atelinae primates and tapirs in particular offer nonredundant seed-dispersal services for many large-seeded Neotropical tree species, which on average have higher wood density than smaller-seeded and winddispersed trees. We used field data and models to project the spatial impact of hunting on large primates by ∼1 million rural households throughout the Brazilian Amazon. We then used a unique baseline dataset on 2,345 1-ha tree plots arrayed across the Brazilian Amazon to model changes in aboveground forest biomass under different scenarios of hunting-induced large-bodied frugivore extirpation. We project that defaunation of the most harvest-sensitive species will lead to losses in aboveground biomass of between 2.5-5.8% on average, with some losses as high as 26.5-37.8%. These findings highlight an urgent need to manage the sustainability of game hunting in both protected and unprotected tropical forests, and place full biodiversity integrity, including populations of large frugivorous vertebrates, firmly in the agenda of reducing emissions from deforestation and forest degradation (REDD+) programs.
Keywords: Biodiversity; Biomass; Carbon Storage; Food Security; Forest; Forest Dynamics; Neotropics; Nonhuman; Population Density; Priority Journal; Seed Dispersal; Soil Fertility; Spider Monkey; Symbiosis; Tropical Rain Forest; Animals; Animals Dispersal; Carbon Cycle; Carnivory; Ecosystem; Endangered Species; Environmental Protection; Fruit; Growth, Development And Aging; Herbivory; Human; Human Activities; Plant Dispersal; Platyrrhini; Predation; Tree; Animals Distribution; Animal; Biodiversity; Biomass; Carbon Cycle; Carnivory; Conservation Of Natural Resources; Ecosystem; Endangered Species; Forests; Fruit; Herbivory; Human Activities; Humans; Plant Dispersal; Platyrrhini; Predatory Behavior; Seed Dispersal; Trees